Compostability assessment of nano-reinforced poly(lactic acid) films. (February 2016) - Balaguer, M.P.; Aliaga, C.; Fito, C.; Hortal, M.
Graphical abstract: Highlights: It evaluates the compostability of nano-reinforced PLA films (Clay, CaCO3, SiO2 ). Disintegration, biodegradability and compost quality are evaluated. Films completely disintegrated into visually indistinguishable residues. Biodegradation is enhanced by nanoparticles. No significant differences are observed in compost quality. Abstract: Nanomaterials can provide plastics with great advantages on mechanical and active properties (i.e. release and capture of specific substances). Therefore, packaging is expected to become one of the leading applications for these substances by 2020. There are some applications already in the market. Nevertheless, there is still some areas under development. A key issue to be analyzed is the end-of-life of these materials once they become waste, and specifically when nanomaterials are used in biodegradable products. The present study evaluated the disintegration, biodegradability, and ecotoxicity of poly(lactic acid) films reinforced with the three following nanomaterials: (1) montmorillonite modified with an ammonium quaternary salt, (2) calcium carbonate and (3) silicon dioxide. Results on disintegration showed that films completely disintegrated into visually indistinguishable residues after 6–7 weeks of incubation in composting environment. Moreover, no differences were observed in the evolution of the bioresidue with respect to color, aspect, and odor in comparison with the control. It was also observed that nanomaterials did not significantly reduce the level of biodegradability of PLA ( p > 0.05). In fact, biodegradation was higher, without finding significant differences ( p > 0.05), in all the nano-reinforced samples with respect to PLA after 130 days in composting (9.4% in PLA + Nano-SiO2 ; 34.0% in PLA + Clay1; 48.0% in PLA + Nano-CaCO3 ). Finally, no significant differences ( p > 0.05) in ecotoxicity in plants were observed as a result of the incorporation of nanoparticles in the PLA matrix.